Memorandum of understanding between Faculty of Chemical Engineering, Universiti Teknologi MARA and Department of Chemical Engineering, Imperial College of Science Technology and Medicine, London, United Kingdom / Fakulti Kejuruteraan Kimia - Universiti Teknologi MARA, Fakulti Kejuruteraan Kimia (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.